2007
DOI: 10.1016/j.jcrs.2006.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral pachymetry measurements according to age using the Pentacam rotating Scheimpflug camera

Abstract: Using the Pentacam, it was possible to acquire information about corneal thickness across the entire cornea. No correlation was found between increasing age and change in peripheral or CCT. Good reliability was noted for pachymetry measurements decreasing slightly toward the periphery, which was independent of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
2
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 33 publications
6
78
2
8
Order By: Relevance
“…Recent studies have investigated the reliability of central and peripheral corneal thickness measurements using the original rotating Scheimpflug camera system. (Khoramnia et al 2007) found good reliability for pachymetry measurements but the reliability decreased slightly towards the peripheral areas. The mean thicknesses of the apex and the thinnest portion of the cornea were 4.33 lm and 4.49 lm, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies have investigated the reliability of central and peripheral corneal thickness measurements using the original rotating Scheimpflug camera system. (Khoramnia et al 2007) found good reliability for pachymetry measurements but the reliability decreased slightly towards the peripheral areas. The mean thicknesses of the apex and the thinnest portion of the cornea were 4.33 lm and 4.49 lm, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…The latest high-resolution (HR) Scheimpflug camera has a redesigned optic design and is improved to maximally capture 138 000 data points in less than 2 seconds. The original device provides CCT measurements of normal corneas that are reliable and have high agreement with UP (Barkana et al 2005;Lackner et al 2005;O'Donnell & Maldonado-Codina 2005;Khoramnia et al 2007;de Sanctis et al 2007a,b;Shankar et al 2008). To our knowledge, however, there are no reports on the repeatability and reproducibility of CCT by the HR rotating Scheimpflug imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In some of the earlier studies, age had no significant effect on CCT (16)(17)(18)(19)(20)(21)(22). All these reports postulated that the number and race of the subjects, and differences in pachymeter instruments, might affect the results (10).…”
Section: Discussionmentioning
confidence: 96%
“…Bu kalın-lığın altındaki kornealara halka implantasyonu halkanın ekstrüzyonuna, çapraz bağlama tedavisinin ince kornealara yapılması endotelyal dekompansasyona neden olabilmektedir. MKK, AKK ve EİKK normal olgularda 538,51±32,26 µ, 539,62±31,87 µ ve 535,42±33,15 µ olarak bildirilmiştir [6]. 3 aralığın-da bildirilmiştir [9,10,12].…”
Section: Discussionunclassified